Development of three phase back to back converter with current flow control using raspberry Pi microcontroller - Mamat, Ibrahim (2015)
A High-Voltage Direct Current (HVDC) electric power transmission system uses direct current form the bulk transmission of electrical power, in contrast with the common Alternating Current (AC) systems. For a long-distance transmission, HVDC systems may be less expensive and suffer lower electrical losses. The overall HVDC system is call back-to-back converter. Therefore, this project is to design and to develop a back-to-back converter with Proportional-Integrative-derivative (PID) control current that could be applied for the resistive load. The basic structure of the PID controller makes it easy to regulate the process output. The control technique is called a current control technique by comparing the output current with the reference current. Thus, the PID controller will force the output current to follow the reference current by creating and changing the pulse width modulation (PWM) signals. The PID controller is developed and simulated by using MATLAB/Simulink software and then implemented to the hardware by using Raspberry Pi Microcontroller. The result from the simulation shows that, the load current follows the reference current from 0 amperes until 1 amperes and the results from the experiment shows that the output current at the load follows the reference current from 0 amperes until 0.4 amperes. The high sensitivity of current sensor and also due to very low resolution of analogue to digital converter effect the result in this project. The results explanation of the project can be divided into three categories; simulation, open loop control and closed loop control.